2011
DOI: 10.1088/0953-2048/24/10/105017
|View full text |Cite
|
Sign up to set email alerts
|

Elastic recoil detection studies of near-surface hydrogen in cavity-grade niobium

Abstract: Recent studies of the quality factor degradation mechanisms in superconducting RF niobium cavities at high surface magnetic fields revealed that RF performance may depend on the total hydrogen content in the 40 nm thick near-surface layer. Hydrogen distribution in niobium and its near-surface content variations after different chemical surface treatments has been addressed in previous studies. However, only chemical treatments were studied while heat treatments are equally important. In this work we use the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…We attribute the formation of smaller hydrides at 100 K (after 3 h hold at 140 K) to the precipitation of another hydride phase, which has a lower solubility limit than the phase formed at 140 K. This second phase is much smaller, likely due to the low free hydrogen concentration at 100 K. It is unlikely that 120 C baking changes hydrogen concentration, which is also supported by previous studies. 34 It is also supported by our 140 K observations-there is no difference between baked and unbaked samples. Yet, small hydrides at 100 K are formed only on unbaked samples, and thus 120 C baking suppresses the formation of the second phase.…”
Section: Discussionsupporting
confidence: 72%
“…We attribute the formation of smaller hydrides at 100 K (after 3 h hold at 140 K) to the precipitation of another hydride phase, which has a lower solubility limit than the phase formed at 140 K. This second phase is much smaller, likely due to the low free hydrogen concentration at 100 K. It is unlikely that 120 C baking changes hydrogen concentration, which is also supported by previous studies. 34 It is also supported by our 140 K observations-there is no difference between baked and unbaked samples. Yet, small hydrides at 100 K are formed only on unbaked samples, and thus 120 C baking suppresses the formation of the second phase.…”
Section: Discussionsupporting
confidence: 72%
“…In particular, for cavity-grade niobium such hydrogen enrichment at the niobium/oxide interface was reported [4,19,20]. In most of the studies the near-surface hydrogen concentration was found to be only weakly affected by vacuum heat treatments at 600-1000 C typically applied on cavities to mitigate Q disease.…”
Section: Discussionmentioning
confidence: 99%
“…[3]) may be due to the entering of hydrogen into niobium whenever the protective Nb 2 O 5 layer is not present. Some previous studies [10] addressed this issue but detailed understanding is not yet developed.…”
Section: Introductionmentioning
confidence: 99%